Short-Term Effects of Growth Hormone on Lipolysis, Glucose and Amino Acid Metabolism Assessed in Serum and Microdialysate of Healthy Young Men - Krebs, Andreas; Baum, Andreas; Doerfer, Jürgen; Gempel, Klaus; Wurm, Michael; Brichta, Corinna; Sass, Jörn Oliver; Winkler, Karl; Schwab, Karl Otfried (Experimental and Clinical Endocrinology & Diabetes, 2019)
Objective We investigated direct effects of a therapeutic growth hormone dose on lipolysis, glucose and amino acid metabolism.Methods This crossover microdialysis trial involved six healthy male volunteers receiving single subcutaneous injections of both growth hormone (0.035 mg/kg) and placebo (0.9% sodium chloride). The investigation comprised three test days with standard diet. The first day served for adaptation, the second and third one for determining study data during 9 night hours with or without growth hormone. Abdominal subcutaneous microdialysate and blood were continuously collected and forwarded to a separate room next door where hourly taken samples were centrifuged and frozen until analysed.Results Growth hormone achieved the peak serum level after 3 h followed by a plateau-like course for the next 6 h. Glycerol in microdialysate started to rise 2 h following growth hormone injection achieving significance compared to placebo after 9 h (P<0.05). Serum glycerol increased 4 h after growth hormone administration achieving significance after 6 h (P<0.05). Glucose and amino acid concentrations showed neither in microdialysate nor in serum significant differences between growth hormone and placebo. Serum values of insulin and C-peptide revealed no significant difference between growth hormone and placebo.Summary and Conclusion As the result of a high single subcutaneous dose of GH, persistent lipolysis can be shown in continuously collected microdialysate and blood, but no indication for gluconeogenesis or protein anabolism.
Keywords: growth hormone; metabolic effects; pharmacokinetics; microdialysis; glycerol